Gestión de tesorería y la eficiencia de la ejecución presupuestal en la Municipalidad Distrital de Yaquerana periodo 2024 - Grandez Mori, Katherine Jezabel (2025)
This study addresses the relationship between treasury management and the efficiency of budget execution in the District Municipality of Yaquerana for the year 2024, with the objective of determining how the management of the treasury area affects budget efficiency. The approach was used quantitatively, with a non-experimental and cross-sectional methodology, and a descriptive and correlative design. The results revealed that the Pearson correlation was 0.915, with a significance value of 0.000, lower than the critical threshold of 0.05, indicating a statistically significant correlation. In conclusion, the existence of a significant link between the variables scrutinized in the District Municipality of Yaquerana is confirmed, supported by a Pearson correlation value of 0.915 and a significance of 0.000, which exceeds the established significance threshold.